Allocating Blood Products During a Time of Remarkable Shortage. (9th November 2022) - Dent, Edward A; Hamilton, Ellie; Bodeker, Joy; Roback, John; Sullivan, H Cliff
Abstract: The COVID-19 Pandemic adversely impacted the nation's blood supply such that blood suppliers could not fill standing orders. To address the dwindling blood supply, the American Red Cross (ARC) implemented daily thresholds, which distributed red blood cells (RBCs) based on clients' historical blood orders and the ARC's inventory. The threshold system left the blood bank to devise a process to judiciously allocate the reduced RBC supply across our institution. Herein, we describe an internal RBC utilization audit, the data from which we used to devise an algorithm to predict our ability to meet transfusion requirements for operating room (OR) procedures. An OR adjudication committee used our report to prioritize elective surgical cases taking places the following day. Thirty-one non-consecutive days of blood inventory release slips were reviewed across three months of recent transfusions. Weekdays were disproportionally investigated to predict the blood utilization for days with scheduled OR procedures. For all RBCs released, the blood type requested and the final disposition (transfused vs returned to blood bank) of the units were recorded. Average use was calculated as well as interquartile range (IQR) to account for transfusion variability. Utilization data was then used to develop a worksheet-based tool to predict ability to meet RBC requirements. Overall, the hospital transfused an average of 80 RBC units each weekday (IQR: 64-92 units). Approximately 40% of all requested RBC units were released to the OR. In turn, the OR transfused only 39% of the RBCs released to them, which represented 20% of transfusions hospital-wide. The OR requested an average of 41 RBC units each weekday (IQR: 25-57 units). The OR transfused an average of 16 units of RBCs each weekday (IQR: 9-21 units). The outpatient cancer center infusion clinic used less than 15% of total RBCs. The biggest user of RBCs were inpatients, who were transfused 65% of RBCs during the week and 82% of transfusions during the weekend. These percentages and the average-to-third-quartile range were used to devise a blood allocation algorithm to inform the OR if the blood bank could support anticipated use. The data was also used to devise a blood allocation worksheet for the on-call transfusion medicine physicians to predict our ability to provide adequate blood for emergent, non-elective procedures that require transfusion support such as liver transplants and aortic repairs. The audit of RBC disposition informed blood inventory management practices during a time of remarkable shortage. Within the confines of the threshold system, the transfusion medicine service allocated the expected number of units based on historical request and transfusion data to predict whether inventory levels could support scheduled and nonscheduled OR procedures.